Priority directions of the state policy on social and economic protection of the youth in Ukraine - Vasyliev , Andrii (Theory and Practice of Public Administration, 2019)
The contemporary issue of the study of the "state youth policy" is one of the basic elements of the study of public administration science, as Ukraine is witnessing an increase in negative trends, in particular in the spheres of education, vocational training, employment and social protection of youth, manifested primarily in unemployment, the aggravation of social problems, the scale of which grows with the number of young people who have lost or can not find a job. All this testifies to the need for further development and improvement of the state youth policy, its legal basis, and the activation of the executive bodies and local self-government bodies in this area.By investigating the humanitarian sphere, scholars are increasingly focusing on the essence, mechanisms of development, and the processes of improving the state youth policy, since young people play an important role in the socio-economic processes of building a democratic state.It is proved that the most important component of socio-economic protection of young people should be the formation of a professional orientation, selection, training and placement system based on the principles of voluntariness and the possibility of free choice of socially beneficial activities taking into account the interests and abilities of a person.Thus, the reform of the system of socio-economic protection of young people is a multifaceted process. Its purpose is to make a young person as less dependent on the state as possible. It is worth raising the level of organization and technology of servicing the unemployed youth. It necessary to further develop the material and technical basis of the employment service through the creation of an information and reference system for managing the labor market; providing mediation services to employers and unemployed citizens.Further directions for the research could be the development of mechanisms for improving the interaction of institutes of public power and youth organizations, monitoring the state of the youth movement in Ukraine.